Investigating the effect of edge and basal plane surface functionalisation of carbonaceous anodes for alkali metal (Li/Na/K) ion batteries. (15th June 2021) - Olsson, Emilia; Cottom, Jonathon; Au, Heather; Titirici, Maria-Magdalena; Cai, Qiong
Abstract: Alkali metal ion batteries are instrumental in the widespread implementation of electric vehicles, portable electronics, and grid energy storage. From experimental characterisation of hard carbons, these carbon anodes were shown to contain a variety of functional groups. Through density functional theory simulations, the effect of functional groups (O, OH, NH2, and COOH) on edges and basal plane surfaces of carbonaceous materials on the adsorption of lithium, sodium, and potassium are investigated. These simulations show that the functionalisation of H-terminated edges and curved surfaces rather than basal planes is more energetically favourable and thus more likely to be present. Comparison of experimental FTIR and computational vibrational frequency analysis confirmed the occurrence of the investigated functional groups (O, OH, NH2, and COOH) in the synthesised hard carbon materials. Metal adsorption on the functionalised models showed that adsorption energies were stronger on the functionalised basal plane in comparison to the functionalised edge sites and contribute to the metal ion immobilization and consequent irreversible capacity loss. The metal adsorption on the curved surface was further improved by the addition of functional groups, benefitting the initial lithiation/sodiation/potassiation of the carbon anode. Hence, the morphology of the functionalised carbon systems plays an important role in the charge/discharge performance of carbonaceous anodes. Graphical abstract: Image 1 Highlights: XPS and FTIR identify functional groups in hard carbon. Functional groups can adsorb at different carbon motifs. DFT simulations show that functional groups bind strongly to edge sites. Li, Na, and K bind strongly to hydroxyl groups. Functional group type and site play important roles in the charge/discharge process.